Iodine deficiency in pregnancy along a concentration gradient is associated with increased severity of preeclampsia in rural Eastern Cape, South Africa - Charles Bitamazire Businge; Benjamin Longo-Mbenza; Andre Pascal Kengne (BMC, 2022)
Abstract Background Preeclampsia is a leading cause of maternal mortality and morbidity in South Africa. Iodine deficiency in pregnancy, which is amenable to correction through iodine supplementation, has been reported to increase the risk of preeclampsia. However, the association of iodine nutrition status with preeclampsia in South Africa has not been studied. Methods We enrolled 51 randomly selected normotensive pregnant controls at term together with 51 consecutively selected cases of preeclampsia and 51 cases of severe preeclampsia/eclampsia, all in the third trimester, from Mthatha Regional and Nelson Mandela Academic Hospital in the Eastern Cape Province. Urinary iodine concentration (UIC), serum thyroid-stimulating hormone (TSH), triiodothyronine (FT3), thyroxine (FT4) and thyroglobulin (Tg) levels were compared between cases and controls. Results The respective chronological and gestational ages at enrolment for normotensive, preeclampsia and severe preeclampsia/eclampsia participants were: age 23, 24 and 19 years (p = 0.001), and gestational age 38, 34, and 35 weeks (p < 0.001). The median gravidity was 1 for all three groups. The median UIC, FT4, FT3 revealed a decreasing and Tg a rising trend with the severity of preeclampsia (p < 0.05). TSH had a non-significant rising trend (p > 0.05). The respective median values for normotensive, preeclampsia and severe preeclampsia/eclampsia participants were UIC 217.1, 127.7, and 98.8 μg/L; FT4 14.2, 13.7, and 12. pmol/L; FT3 4.8, 4.4, and 4.0 pmol//L; Tg 19.4, 21.4, and 32. Nine microgram per liter; TSH 2.3, 2.3, and 2.5 mIU/L. UIC < 100 μg/L, Tg > 16 μg/L and FT4 < 11.3 pmol/L were independent predictors of preeclampsia/eclampsia syndrome. Conclusion Women with severe preeclampsia/eclampsia had significantly low UIC and high Tg, suggesting protracted inadequate iodine intake. Inadequate iodine intake during pregnancy severe enough to cause elevated Tg and FT4 deficiency was associated with an increased risk of severe preeclampsia/eclampsia.